Advances in Production, Properties and Applications of Sprouted Seeds (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Sprouted grains are food ingredients widely appreciated for their improved nutritional, functional, organoleptic, and textural properties compared with non-germinated grains. In recent years, sprouting has been explored as a promising green food engineering strategy to improve the nutritional value of grains and the formation of secondary metabolites with potential application in the functional food, nutraceutical, pharmaceutical, and cosmetic markets. However, little attention has been paid to the impact of sprouting on the chemical composition, safety aspects, and technofunctional and chemopreventive properties of sprouted seeds and their derived flours and byproducts. The six articles included in this Special Issue present insightful findings on the most recent advances regarding new applications of sprouted seeds or products derived thereof, evaluations of the nutritional value and phytochemical composition of sprouts during production or storage, and explorations of their microbiological, bioactive, and technofunctional properties.